Liquid treatment of food coloring industry waste using coconut and chitosan in removal dyes - Defana Makartina Yusuf; Nur Aini Rahma; Dian Yanuarita Purwaningsih (Universitas Lambung Mangkurat, 2023)
Liquid waste has a component containing water that has been mixed with chemical compounds. One example of liquid waste containing chemical compounds is wastewater from a food coloring industry. The liquid waste of the food coloring industry has a very strong color density so that it has a negative impact on the environment, therefore it is necessary to treat liquid waste in order to meet the quality standards of wastewater in accordance with East Java Governor Regulation number 72 of 2013. The purpose of this study was to determine the effect of adding dose of coagulant and mass of biosorbent on percent color removal in food coloring industrial wastewater. The results showed that the addition of 35% coagulant and 13% biosorbent resulted in 97% optimal removal of color.